STABILITY INDICATING CHIRAL HPLC METHOD FOR THE ESTIMATION OF PIOGLITAZONE ENANTIOMERS IN PHARMACEUTICAL FORMULATION - B, GOWRAMMA; SN, MEYYANATHAN; B, BABU; KRISHNAVENIN; KUMAR KR, SENTHIL (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: A stability indicating chiral high performance liquid chromatographic (HPLC) method was developed and validated for the separated (S) and (R) pioglitazone in raw material and its determination in the presence of degradation products formed during forced degradation studies. Methods: In the present study, an isocratic normal phase-HPLC method was developed with stationary phase as ACI Cellu 1 (150 mm Ã— 4.6 mm i.d., 5Â Î¼)Â columnÂ andÂ n-hexane:Â N-propylÂ alcoholÂ (80:20,Â V/V)Â asÂ mobileÂ phase.Â TheÂ entireÂ studyÂ wasÂ performedÂ usingÂ 1.0Â ml/minuteÂ asÂ flowÂ rateÂ andÂ theÂ detectionÂ wavelengthÂ atÂ 233Â nm.Â TheÂ pioglitazoneÂ (RÂ andÂ S)Â wasÂ exposedÂ toÂ variousÂ stressÂ conditionÂ suchÂ asÂ hydrolyticÂ (acidÂ andÂ base),Â neutral,Â oxidative,Â andÂ photolytic.Â TheÂ stressedÂ samplesÂ wereÂ analyzedÂ byÂ theÂ proposedÂ method. Result:Â TheÂ describedÂ methodÂ wasÂ linearÂ overÂ theÂ rangeÂ ofÂ 5-15Â Âµg/mlÂ forÂ R-pioglitazoneÂ andÂ 4-14Â Âµg/mlÂ forÂ S-pioglitazone.Â TheÂ limitÂ ofÂ detectionÂ andÂ limitÂ ofÂ quantificationÂ ofÂ S-pioglitazoneÂ andÂ R-pioglitazoneÂ wereÂ foundÂ toÂ beÂ 1.4Â Î¼g/mlÂ andÂ 4.26Â Î¼g/ml,Â respectively.Â TheÂ recoveryÂ studyÂ ofÂ SÂ andÂ R-Pioglitazone from tablets formulation ranged from 97.14% to 100.04%, respectively. Conclusion:Â TheÂ developedÂ methodÂ canÂ beÂ appliedÂ inÂ theÂ qualityÂ controlÂ ofÂ drugÂ products. Keywords:Â Stability-indicatingÂ method,Â Validation,Â Chiral,Â Pioglitazone.